Pengembangan Komik Sebagai Media Pembelajaran Pada Mata Kuliah Sistem Komunikasi Optik di Prodi Pendidikan Teknik Elektronika UNJ - Prasetyo, Wahyu; Maruddani, Baso (PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA, 2022)
The research aims to develop comic learning media in the Optical Communication System course for students of the Electronic Engineering Education Study Program, State University of Jakarta, as well as to test the feasibility level based on material experts, media experts and students. This study uses the Research and Development (RnD) method with the Hannafin and Peck model which includes; 1) requirements analysis, 2) design, 3) development and implementation. The results of the development of comic learning media in the Optical Communication System course are used in Standard, Architecture and Power Calculation materials for GPON, GPON Backhaul for LTE/LTE-A, and GPON as 5G Backhaul. The results of research and development are 1) comic learning media in the Optical Communication System course for students of the Electronic Engineering Education Study Program UNJ which has been developed based on the Research and Development (RnD) method with the Hannafin and Peck model. The resulting product is a web comic into 43 pages and can be accessed at https://fliphtml5.com/crfdj/oteq. 2) The results of the feasibility test by material experts obtained an assessment percentage of 81.6%, meaning that the product was very feasible. 3) The results of the feasibility test by media experts obtained an assessment percentage of 95.6%, meaning that the product was very feasible. 4) field trials to students of the Electronic Engineering Education Study Program UNJ in the Optical Communication System course obtained an assessment percentage of 85%. Based on the feasibility category, it can be concluded that the comic learning media developed in the Optical Communication System course can be categorized as very feasible to be used as learning media